Large capital infusions, investor reactions, and the return and risk-performance of financial institutions over the business cycle - Elyasiani, Elyas; Mester, Loretta J.; Pagano, Michael S. (Journal of Financial Stability, 2014)
We examine investors’ reactions to announcements of large capital infusions by U.S. financial institutions (FIs) from 2000 to 2009. These infusions include private market infusions (seasoned equity offerings (SEOs)) as well as injections of government capital under the Troubled Asset Relief Program (TARP). The sample period covers both business cycle expansions and contractions, and the recent financial crisis. We present evidence on the factors affecting FIs’ decisions to raise capital, the determinants of investor reactions, and post-infusion risk-taking of the recipients, as well as a sample of matching FIs. Investors reacted negatively to the news of private market SEOs by FIs, both in the immediate term (e.g., the two days surrounding the announcement) and over the subsequent year, but positively to TARP injections. Reactions differed depending on the characteristics of the FIs, and the stage of the business cycle. Smaller, more financially constrained non-bank institutions were more likely to have raised capital through private market offerings during the period prior to TARP, and firms receiving a TARP injection tended to be riskier and more levered. In the case of TARP recipients, they appeared to finance an increase in credit risk with more stable financing sources such as core deposits, which lowered their liquidity risk. However, we find no evidence that banks’ capital adequacy increased after the capital injections.